A Linguistic Analysis of AEC News in an English Newspaper for Language Learning and Teaching - Kumsorn, Praochompoo (Journal of Education and Vocational Research, 2014)
An English newspaper, as an authentic English resource, provides a view of global knowledge and English usage in a physical world as it contains manifold issues and discourses valuable for English teaching and learning in a contemporary classroom. This study employed Systemic Functional Grammar of Halliday’s approach to analyze texts of news linguistically. The purposes of the study were 1) to explore prevalent topics of AEC news as a reflection of Thailand and communicative purposes for the upcoming ASEAN Economic Community in 2015, 2) to specifically analyze grammatical sentence structures used in an English newspaper aiming for English teaching and learning in Thai context. AEC news’ articles were chosen for this study as it has become a considerably important event which shares multilateral information to ASEAN country members. The Nation newspaper was chosen for data collection for the period from January to August, 2013. Results showed that economics, tourism, and transportation were the most important topics and were reflective of Thailand’s movement towards AEC. The news was mostly organized the idea by particular to general technique and mainly conveyed to the readers with informing as a communicative purpose. The most prevalent sentence structures were complex sentence. Active voice was more prevalent than Passive voice. The conclusion of the study was drawn descriptively. This study implicated that an English newspaper was beneficial for English teaching and learning as it contained a variety of language usage that could be used as a teaching material to improve students’ grammatical and writing skills.